Migraine with aura is not linked to the FHM gene CACNA1A or the chromosomal region, 19p13. - Noble-Topham, SE; Dyment, D; Cader, M; Ganapathy, R; Brown, J; Rice, G; Ebers, G (2002)
Two microsatellite markers, tightly linked to CACNA1A, were genotyped in migraine with aura (MA) families to determine if this gene, which underlies the 19p13 linked forms of familial hemiplegic migraine, is also linked to MA. Two-point parametric lod and nonparametric linkage scores did not support linkage. Transmission disequilibrium testing provided no evidence for linkage of MA to CACNA1A. In a large dataset of 64 Canadian MA families, the authors did not find evidence to support an MA susceptibility gene in the region of 19p13.